Effects of a Short Drilling Implant Protocol on Osteotomy Site Temperature and Drill Torque. Issue 1 (February 2018) - Mihali, Sorin G.; Canjau, Silvana; Cernescu, Anghel; Bortun, Cristina M.; Wang, Hom-Lay; Bratu, Emanuel
Abstract : Purpose: To establish a protocol for reducing the drilling sequence during implant site preparation based on temperature and insertion torque. The traditional conventional drilling sequence (used several drills with 0.6-mm increment each time) was compared with the proposed short drilling protocol (only used 2 drills: initial and final drill). Materials and Methods: One hundred drilling osteotomies were performed in bovine and porcine bones. Sets of 2 osteotomy sites were created in 5 bone densities using 2 types of drilling protocols. Thermographic pictures were captured throughout all drilling procedures and analyzed using ThermaCAM Researcher Professional 2.10. Torque values were determined during drilling by measuring electrical input and drill speed. Results: There were statistically significant differences in bone temperature between the conventional and short drilling protocols during implant site preparation (analysis of variance P = 0.0008). However, there were no significant differences between the 2 types of drilling protocols for both implant diameters. Implant site preparation time was significantly reduced when using the short drilling protocol compared with the conventional drilling protocol ( P < 0.001). Conclusions: Within the limitations of the study, the short drilling protocol proposed herein may represent a safe approach for implant site preparation.